20. Jahrhundert mit beschränkter Haftung: Kapital, Arbeit und Bürokratie im Zeitalter des Nationalismus - O’Connor, James (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
With the aid of three categories - which are not only meant geographically -"West" (Western Europe and North America), "East" (Eastern Europe) and "South" (the Third World), the main features of the transformation processes ofthe 20th century are analysed: the interrelations between capital, labor and community, the development and integration of the different oppositional movements, the rise of bureaucracy and the welfare state and their following decline, the importance of nationalism and national states and the transition to a global capitalism.